Mild hemophilia in a competitive high school soccer player: A case report - Omole, O.; Reed, J.; Dunn, A. L.; Gleason, C. N. (Journal of Athletic Training, 2023)
In this report, we discuss the case of a now 23-year-old athlete who was diagnosed with mild hemophilia, successfully played varsity soccer throughout high school, and continued to play intramural and club soccer while in college. A prophylactic protocol was developed by the athlete`s hematologist to allow his safe participation in contact sports. Similar prophylactic protocols have been discussed by Maffet et al that successfully allowed an athlete to participate in high-level basketball. However, significant barriers still exist for an athlete with hemophilia who wants to engage in contact sports. We discussed how athletes with adequate support networks can participate in contact sports. Decisions need to be made on a case-by-case basis and involve the athlete, family, team, and medical personnel.